Ylasmerybceo six-element rare earth high-entropy oxide photocatalytic material and preparation method and uranium removal application thereof
Patent Information
- Application Number
- CN202611101849.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
也正因为其灵活、多样的复杂体系,导致稀土成分和配比更加难以把控,材料在复杂水环境中的稳定性也很难把控
[0028]1、本发明通过精准设计Y、La、Sm、Er、Yb、Ce六种稀土元素组成的高熵体系,旨在实现以下目标:
Smart Images

Figure CN122999168A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalytic materials and radioactive wastewater treatment technology, specifically involving YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic materials, their preparation methods, and their application in uranium removal. Background Technology
[0002] Uranium-containing radioactive wastewater generated during uranium mining and smelting, and the nuclear fuel cycle poses a serious threat to the ecological environment and public health. Photocatalytic reduction technology can reduce soluble U(VI) to insoluble U(IV) precipitate, which is an environmentally friendly and energy-efficient strategy for uranium separation and fixation. However, traditional photocatalysts suffer from problems such as high recombination rate of photogenerated carriers, low visible light utilization, and poor stability, making them difficult to handle complex real-world wastewater environments.
[0003] High-entropy materials (HEMs) offer novel insights for designing high-performance photocatalysts due to their high-entropy effect, lattice distortion effect, slow diffusion effect, and cocktail effect. Among them, high-entropy oxides (HEOs) have attracted significant attention due to their strong compositional tunability, high chemical stability, and abundant defect chemistry. Rare-earth-based HEMs, in particular, exhibit unique potential in light absorption, charge separation, and surface reaction regulation due to their diverse 4f electron configurations, tunable ionic radii, and flexible valence states. However, their flexible and diverse complex systems also make it more difficult to control the rare-earth composition and ratio, and the stability of the materials in complex aquatic environments is also challenging to manage.
[0004] In addition, existing photocatalytic materials also face the challenge of balancing "high defect concentration" and "high crystallinity".
[0005] Therefore, developing a six-membered rare earth high-entropy oxide photocatalytic material with high crystallinity, abundant defect concentration, high photogenerated carrier separation efficiency, and excellent stability in complex aquatic environments, as well as its controllable preparation method, and applying it to the photocatalytic removal of uranyl ions, is an urgent problem to be solved. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a six-element rare earth high-entropy oxide photocatalytic material (YLaSmErYbCeO), its preparation method, and its application in uranium removal. By precisely designing a high-entropy system composed of six rare earth elements (Y, La, Sm, Er, Yb, Ce), a six-element rare earth high-entropy oxide photocatalytic material with high crystallinity, abundant defect concentration, high photogenerated carrier separation efficiency, and excellent stability in complex aquatic environments can be obtained.
[0007] The technical solution of the present invention is as follows:
[0008] The preparation method of YLaSmErYbCeO hexa-membered rare earth high-entropy oxide photocatalytic material includes the following steps:
[0009] (1) Take rare earth salts and add them to a solvent, and stir to form a homogeneous rare earth salt solution, wherein the rare earths include Y, La, Sm, Er, Yb and Ce;
[0010] (2) Add hydrothermal auxiliary agent to the rare earth salt solution obtained in step (1), mix well, and obtain a mixed solution;
[0011] (3) The mixed solution obtained in step (2) is subjected to hydrothermal reaction. After the reaction is completed, it is naturally cooled, the precipitate is collected, washed and dried to obtain precursor powder;
[0012] (4) Heat-treat the precursor powder obtained in step (3) to obtain the YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material.
[0013] Preferably, in step (1), the salt is any one or more of nitrates, chlorides, sulfates, acetates, acetylacetones, and carbonates, the molar ratio of Y, La, Sm, Er, Yb, and Ce is (1~5):(1~5):(1~5):(1~5):(1~5):(1~5), the solvent is one or more of water, ethanol, methanol, N,N-dimethylformamide, and dioxane, and the ratio of the molar amount of the rare earth salt to the volume of solvent added is 1 mmol:(3~10) mL.
[0014] More preferably, in step (1), the salt is a nitrate, the molar ratio of Y, La, Sm, Er, Yb and Ce is 1:1:1:1:1:1, and the solvent is water.
[0015] More preferably, the rare earth salts include Y(NO3)3·4H2O, La(NO3)3·6H2O, Sm(NO3)3·6H2O, Er(NO3)3·5H2O, Yb(NO3)3·5H2O, and Ce(NO3)3·6H2O.
[0016] Preferably, in step (2), the hydrothermal auxiliary agent is urea (which also serves as a precipitant and pH adjuster), and the molar ratio of urea to rare earth salt is not less than 2:1.
[0017] The mixing method includes ultrasonic mixing for 8-20 minutes.
[0018] Preferably, in step (3), the conditions for the hydrothermal reaction include: temperature 100~150℃ and time 12~48h.
[0019] The washing process specifically includes washing with deionized water and anhydrous ethanol alternately 2 to 4 times.
[0020] The drying process specifically includes drying at 50~70℃ for 8~20 hours.
[0021] Preferably, the heat treatment conditions in step (4) include: air atmosphere, heating rate of 0.3~1.0℃ / min, temperature of 500~800℃, and holding time of 8~15h.
[0022] More preferably, the heat treatment conditions in step (4) include: a heating rate of 0.5~0.8℃ / min, a temperature of 550~650℃, and a holding time of 9~12h. More preferably, the heating rate is 0.5℃ / min, the temperature is 600℃, and the holding time is 10h. Under these conditions, a six-membered high-entropy oxide with a single fluorite structure, high crystallinity, and rich in oxygen vacancies can be obtained.
[0023] The present invention also provides a YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material obtained by the above preparation method.
[0024] This invention also provides an application of YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material for removing uranyl ions.
[0025] Preferably, the YLaSmErYbCeO hexavalent rare earth high-entropy oxide photocatalytic material is placed in wastewater containing uranyl ions and subjected to a photocatalytic reaction under light irradiation to reduce hexavalent uranium to tetravalent uranium, thereby achieving the separation and enrichment of uranyl ions.
[0026] Preferably, the concentration of uranyl ions in the wastewater is 10~500 mg / L, and the amount of the YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material added is 200~800 mg / L.
[0027] Technical effects of the present invention:
[0028] 1. This invention aims to achieve the following objectives by precisely designing a high-entropy system composed of six rare earth elements: Y, La, Sm, Er, Yb, and Ce:
[0029] (1) Optimize light absorption and charge separation performance: broaden the visible light response range by band engineering control of rare earth elements; use defects in high-entropy lattice as electron trapping centers to suppress photogenerated carrier recombination.
[0030] (2) Enhance environmental adaptability and cycle stability: With the inherent chemical stability and slow diffusion effect of high-entropy materials, the durability of materials in harsh water environments such as high ionic strength and wide pH range is ensured.
[0031] 2. This invention successfully breaks the traditional trade-off in material performance: through high-entropy design, a hexa-element rare earth high-entropy oxide with high crystallinity (single fluorite phase, sharp XRD diffraction peaks) was obtained under heat treatment at a specific temperature (550~650℃), achieving a synergistic improvement in structural stability and reactivity.
[0032] 3. The hexa-element rare earth high-entropy oxide of the present invention has excellent photocatalytic uranium removal performance: in a 50 mg / L uranyl solution at pH 5.5, the optimal sample can achieve complete removal of U(VI) within 45 minutes, and maintains good activity in both high ionic strength (0.3 M NaCl) and wide pH range (4.5-6.5).
[0033] 4. The hexa-element rare earth high-entropy oxide of the present invention has good structural stability and performance: the high-entropy effect and slow diffusion effect endow the material with excellent chemical stability, diverse 4f electron configuration, adjustable ionic radius and flexible valence state, which meet the needs of practical applications.
[0034] 5. The preparation process of the present invention is simple and reproducible: it adopts a two-step method of urea-assisted hydrothermal coprecipitation combined with controllable heat treatment. The process conditions are mild and easy to scale up, making it suitable for large-scale preparation. Attached Figure Description
[0035] Figure 1 XRD patterns of oxide materials with different rare earth components;
[0036] Figure 2 EPR test spectra of oxide materials with different rare earth components;
[0037] Figure 3 The XRD patterns of the precursor powder (before sintering) and the sample HEO-600 (after sintering) in Example 1 of this invention are shown.
[0038] Figure 4 The XRD patterns of YLaSmErYbCeO materials obtained in Examples 1-4 of this invention are shown below.
[0039] Figure 5 The XRD pattern (left) and structural simulation diagram (right) of the YLaSmErYbCeO material prepared in Example 1 of this invention are shown.
[0040] Figure 6 The images shown are transmission electron microscope (TEM) images of the YLaSmErYbCeO material prepared in Example 1 of this invention (A is the TEM image of the material, B is the result of fast Fourier transform of the selected region in A, and the rest are the scanning TEM combined with X-ray energy dispersive spectroscopy analysis results of the seven elements Y, La, Sm, Er, Yb, Ce and O).
[0041] Figure 7 The photocatalytic uranium removal performance of the YLaSmErYbCeO materials prepared in Examples 1-4 of this invention at different times;
[0042] Figure 8 The photocatalytic uranium removal performance of the YLaSmErYbCeO material prepared in Example 1 of this invention under different pH conditions;
[0043] Figure 9 The photocatalytic uranium removal performance of the YLaSmErYbCeO material prepared in Example 1 of this invention under different ionic intensities;
[0044] Figure 10 The photocatalytic uranium removal performance of the YLaSmErYbCeO material prepared in Example 1 of this invention under the influence of different competing ions;
[0045] Figure 11 The photocatalytic uranium removal performance of YLaSmErYbCeO materials prepared in Example 1 and Comparative Examples 1-18 of the present invention is shown (wherein, numbers 1-18 correspond to Comparative Examples 1-18 respectively, and C corresponds to Example 1). Detailed Implementation
[0046] The above-mentioned solution will be further described below with reference to specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0047] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0048] It should be noted that the material nature of the hexa-element rare earth high-entropy oxide photocatalytic material of the present invention is not affected by the naming order or format of rare earth elements. As long as it is a hexa-element rare earth high-entropy oxide composed of the six rare earth elements Y, La, Sm, Er, Yb and Ce (such as YLaSmErYbCeO hexa-element rare earth high-entropy oxide, CeSmYbErYLaO hexa-element rare earth high-entropy oxide, CeSmYbErYLa-O hexa-element rare earth high-entropy oxide, etc.), it falls within the protection scope of the hexa-element rare earth high-entropy oxide photocatalytic material of the present invention.
[0049] Example 1
[0050] Equal molar amounts of six rare earth nitrates, including 1 mmol of Y(NO3)3·4H2O, 1 mmol of La(NO3)3·6H2O, 1 mol of Sm(NO3)3·6H2O, 1 mmol of Er(NO3)3·5H2O, 1 mmol of Yb(NO3)3·5H2O, and 1 mmol of Ce(NO3)3·6H2O, were weighed and added to 30 mL of deionized water. The mixture was sonicated to dissolve and form a homogeneous solution. 2 mmol of urea was added, and the mixture was sonicated for 10 min. The resulting solution was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and subjected to hydrothermal reaction at 100 °C for 24 hours. After the reaction, the mixture was allowed to cool naturally, and the precipitate was collected by centrifugation. The precipitate was washed three times alternately with deionized water and anhydrous ethanol, and then dried at 60 °C for 12 hours to obtain the precursor powder. The precursor powder was heated to 600℃ in air at a rate of 0.5℃ / min and held for 10 hours. After cooling in the furnace, the YLaSmErYbCeO hexa-element rare earth high-entropy oxide photocatalytic material (sample HEO-600) was obtained.
[0051] Example 2
[0052] The difference between this embodiment and Embodiment 1 is that the heat treatment temperature of 600℃ is changed to 500℃ to obtain the photocatalytic material sample HEO-500.
[0053] Example 3
[0054] The difference between this embodiment and Embodiment 1 is that the heat treatment temperature of 600℃ is changed to 700℃ to obtain the photocatalytic material sample HEO-700.
[0055] Example 4
[0056] The difference between this embodiment and Embodiment 1 is that the heat treatment temperature of 600℃ is changed to 800℃ to obtain the photocatalytic material sample HEO-800.
[0057] Comparative Examples 1-18
[0058] Six rare earth nitrates, including Y(NO3)3·4H2O, La(NO3)3·6H2O, Sm(NO3)3·6H2O, Er(NO3)3·5H2O, Yb(NO3)3·5H2O, and Ce(NO3)3·6H2O, were weighed according to the corresponding molar amounts in Table 1. They were added to 30 mL of deionized water and sonicated to form a homogeneous solution. 2 mmol of urea was added, and the mixture was sonicated for 10 min. The resulting solution was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 100 °C for 24 hours. After the reaction, the mixture was allowed to cool naturally, and the precipitate was collected by centrifugation. The precipitate was washed three times alternately with deionized water and anhydrous ethanol, and dried at 60 °C for 12 hours to obtain precursor powder. The precursor powder was heated to 600 °C at a rate of 0.5 °C / min in air and held at that temperature for 10 hours. After furnace cooling, different YLaSmErYbCeO hexavalent rare earth high-entropy oxide photocatalytic materials were obtained.
[0059] Table 1. Rare earth nitrate addition amounts in Example 1 and Comparative Examples 1-18
[0060] Example 1 1mmol 1mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 1 0 mmol 1mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 2 1mmol 0 mmol 1mmol 1mmol 1mmol 1mmol Example 3 1mmol 1mmol 0 mmol 1mmol 1mmol 1mmol Comparative Example 4 1mmol 1mmol 1mmol 0 mmol 1mmol 1mmol Comparative Example 5 1mmol 1mmol 1mmol 1mmol 0 mmol 1mmol Comparative Example 6 1mmol 1mmol 1mmol 1mmol 1mmol 0 mmol Comparative Example 7 0.5mmol 1mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 8 2mmol 1mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 9 1mmol 0.5mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 10 1mmol 2mmol 1mmol 1mmol 1mmol 1mmol Comparative Example 11 1mmol 1mmol 0.5mmol 1mmol 1mmol 1mmol Comparative Example 12 1mmol 1mmol 2mmol 1mmol 1mmol 1mmol Comparative Example 13 1mmol 1mmol 1mmol 0.5mmol 1mmol 1mmol Comparative Example 14 1mmol 1mmol 1mmol 2mmol 1mmol 1mmol Comparative Example 15 1mmol 1mmol 1mmol 1mmol 0.5mmol 1mmol Comparative Example 16 1mmol 1mmol 1mmol 1mmol 2mmol 1mmol Comparative Example 17 1mmol 1mmol 1mmol 1mmol 1mmol 0.5mmol Comparative Example 18 1mmol 1mmol 1mmol 1mmol 1mmol 2mmol
[0061] I. The Influence of Different Rare Earth Components on Oxide Materials
[0062] 1. Research on the formation of the high entropy effect in this invention
[0063] To investigate the unique role of the high-entropy effect in the crystal formation process, this invention selected different rare earth components according to the preparation method of Example 1, and prepared a series of comparative samples, namely, mono-rare earth oxide (Ce-O), binary rare earth oxide (CeSm-O), ternary rare earth oxide (CeSmYb-O), quaternary rare earth oxide (CeSmYbEr-O), pentagonal rare earth high-entropy oxide (CeSmYbErY-O), and hexa-rare earth high-entropy oxide (CeSmYbErYLa-O), and performed XRD characterization.
[0064] The evolution pattern of its XRD pattern is as follows: Figure 1 As shown, a non-monotonic "V"-shaped trend emerges. When the number of metal components increases from one (low entropy) to four (medium entropy), the diffraction peak intensity gradually weakens, while the full width at half maximum (FWHM) continues to increase, indicating a significant deterioration in crystallinity, approaching an amorphous state near the quaternary component. This phenomenon aligns with classical understanding: the introduction of multiple large-size differentially distributed cations generates severe lattice stress and distortion, hindering the establishment of long-range ordered structures. However, when the number of components exceeds the threshold and increases to five or six (high entropy), the diffraction peak intensity dramatically and abruptly increases, the peak shape becomes sharp again, and the crystallinity recovers or even surpasses that of some binary and ternary samples. This reversal phenomenon is direct evidence of the high-entropy stabilization effect: when the configuration entropy (ΔS) increases... confWhen the value is sufficiently high, the thermodynamic driving force it provides (-TΔS) conf This is sufficient to overcome the inherent lattice distortion energy (ΔH) of a multi-element system. mix This leads to a thermodynamic tendency to form an ordered single solid solution phase rather than a disordered amorphous or multiphase mixture. This represents the first time in this system that a leap from "entropy-induced disorder" to "entropy-induced order" has been achieved, laying the structural foundation for obtaining materials with both high crystallinity and high defect concentration.
[0065] 2. Oxygen vacancy defects in the material of this invention
[0066] To characterize the oxygen vacancy defects in the materials of this invention, quantitative EPR tests were performed on materials with different rare earth compositions. The results are shown below. Figure 2 A symmetrical Lorentz line signal was observed in all samples at a g value of approximately 2.003. This signal is widely considered to be the characteristic signal of paramagnetic centers formed after oxygen vacancies trap single electrons. Quantitative integration of the signal intensity revealed a monotonically and dramatically increasing enhancement with increasing compositional entropy. This result demonstrates that the high-entropy design strategy successfully created abundant oxygen vacancy defects within the material.
[0067] II. Effects of Heat Treatment on YLaSmErYbCeO Hexa-Element Rare Earth High-Entropy Oxide Photocatalysts
[0068] 1. Comparison of X-ray diffraction (XRD) patterns before and after heat treatment (sintering)
[0069] The precursor powder from Example 1 (before sintering) and the final photocatalytic material sample HEO-600 (after sintering) were subjected to XRD pattern analysis, and the results are shown in the figure. Figure 3 It can be seen that the amorphous multi-ion precursor precipitate before sintering is transformed into the target high-entropy oxide crystalline phase during the sintering process.
[0070] 2. Comparison of X-ray diffraction (XRD) patterns at different heat treatment temperatures
[0071] The YLaSmErYbCeO materials prepared at different heat treatment temperatures in Examples 1-4 were subjected to XRD patterns, and the results are shown below. Figure 4After calcination at 500℃, the product exhibited obvious oxide crystalline phase characteristics, but with relatively low crystallinity. As the temperature increased to 600℃, all diffraction peaks became sharp and intense, clearly belonging to a single fluorite structure, and no impurity phase peaks appeared, indicating that a well-crystallized high-entropy oxide single phase had been successfully formed. When the temperature continued to rise to 700℃ and 800℃, weak second-phase diffraction peaks began to appear in the XRD patterns of some samples. Excessively high temperatures may induce local elemental segregation or phase transformation, compromising the stability of the high-entropy single phase. Based on the XRD phase analysis results, 600℃ was determined to be the optimal heat treatment temperature. The sample synthesized at this temperature achieved the best balance between phase purity and crystallinity, fully meeting the requirements of a high-entropy single-phase solid solution. Therefore, HEO-600 was selected for subsequent characterization and performance testing.
[0072] III. Characterization of the YLaSmErYbCeO material of the present invention
[0073] 1. Fine-grained structural analysis
[0074] The HEO material prepared in Example 1 of this invention underwent fine structural analysis, and the results are shown in the figure. Figure 5 All diffraction peaks in the X-ray diffraction (XRD) pattern corresponded perfectly to the standard spectrum of the cubic fluorite structure (space group: Fm-3m), with sharp and symmetrical peak shapes and no identifiable impurity phase diffraction peaks, initially indicating the formation of a single phase. To obtain precise crystallographic parameters, Rietveld full-spectrum structure refinement was performed (see...). Figure 5 (Left), the refined results show that the experimental data and the data based on the ideal fluorite structure model (see left) are consistent. Figure 5 The calculated spectrum (right) shows a high degree of agreement, and the reliability factor R is refined. wp and R p All are at a low level. This result conclusively confirms from the perspective of long-range order that six rare earth elements (Y, La, Sm, Er, Yb, Ce) with different ionic radii have been successfully dissolved in a unified fluorite lattice, forming a thermodynamically stable single-phase high-entropy solid solution.
[0075] 2. Transmission electron microscopy image analysis
[0076] The HEO material prepared in Example 1 of this invention was measured by transmission electron microscopy, and the results are shown in the figure. Figure 6 It reveals the microstructure of the material (see Figure 6 (A) The HEO material consists of well-dispersed, uniformly sized, nearly spherical nanoparticles with a statistically average particle size of 190 ± 15 nm. This regular morphology is beneficial for light scattering and absorption. A sharp diffraction spot was obtained by performing a Fast Fourier Transform (FFT) on a selected region, which can be labeled as projection along the
[100] zone axis, confirming that these nanoparticles have good single-crystal properties (see A). Figure 6 (B in the text). Scanning transmission electron microscopy combined with X-ray energy dispersive spectroscopy analysis showed that the seven elements Y, La, Sm, Er, Yb, Ce, and O were highly uniformly distributed within individual nanospheres and between different particles, with no enrichment regions or segregation of any elements. This directly verified the high-entropy characteristics of atomic-level mixing at the nanoscale (see B). Figure 6 (The remaining figures in the text).
[0077] IV. Photocatalytic uranium removal performance of YLaSmErYbCeO materials
[0078] 20 mg of different HEO materials prepared according to this invention were added to 50 mL of uranyl solution with an initial concentration of 50 mg / L C0 and pH=5.5, and photocatalytic reaction was carried out under irradiation with a 300 W xenon lamp. Samples were taken and filtered at regular intervals, and the U(VI) concentration Ct in the solution was measured. The remaining uranium ratio Ct / C0 and the uranium removal rate were calculated. Uranium removal rate (%) = 100% × (1 - Ct / C0).
[0079] 1. Effect of heat treatment temperature on the photocatalytic uranium removal performance of materials
[0080] The catalytic performance of a material is closely related to its microstructure. This invention first investigated the effect of different heat treatment temperatures (500℃, 600℃, 700℃, 800℃) on the photocatalytic uranium removal activity of HEO materials in Examples 1-4. The results are shown below. Figure 7 All samples exhibited photocatalytic activity, but their performance varied significantly. The sample heat-treated at 600℃ showed the best activity, achieving complete removal of U(VI) within 45 minutes. This optimal performance corresponds perfectly to the optimal crystallinity and pure single-phase fluorite structure shown in XRD characterization. Temperatures that are too low (500℃) may lead to incomplete crystallization and insufficient exposure of active sites; temperatures that are too high (700℃, 800℃) may cause oxygen vacancy annihilation or induce lattice shrinkage and elemental segregation, resulting in decreased activity. These results confirm that 600℃ is the optimal preparation condition for balancing high crystallinity and high concentration of active defects.
[0081] 2. Effect of different pH uranyl solutions on the photocatalytic uranium removal performance of the material
[0082] The pH value of uranyl solution significantly affects the species distribution of U(VI), the surface charge of the catalyst, and the interfacial reaction process. This application tested the uranium removal performance of the HEO material prepared in Example 1 under pH conditions of 4.5–6.5, and the results are shown below. Figure 8(The numbers following the pH values in the figure indicate the remaining uranium percentage at 90 min). The HEO material maintained good activity across a wide pH range tested, demonstrating its broad applicability. Kinetic analysis showed the fastest reaction rate at pH = 5.5. This is likely because near this pH, U(VI) primarily reacts as the highly reactive UO2. 2+ The presence of free ions and the surface charge state of the catalyst are conducive to interfacial electron transfer or the effective generation and contact of reactive oxygen species.
[0083] 3. Effect of different ionic strengths on the photocatalytic uranium removal performance of the material
[0084] To simulate a high-salinity wastewater environment, this invention investigated the effect of background electrolyte concentration (as NaCl) on the photocatalytic reaction of the HEO material prepared in Example 1. Comparative experiments were conducted in deionized water (Control), 0.1 M NaCl solution, and 0.3 M NaCl solution. The results are shown in [Figure Number]. Figure 9 High ionic strength slows down the initial reaction rate, but all systems eventually achieve similar levels of complete removal. Increased ionic strength compresses the electrical double layer at the solid-liquid interface, potentially slightly affecting the mass transfer and adsorption behavior of reactants or intermediates, thus altering the apparent kinetics in the early stages of the reaction, while its thermodynamic equilibrium remains largely unaffected.
[0085] 4. Effects of different competing ions on the photocatalytic uranium removal performance of the material
[0086] Real-world water bodies often contain multiple coexisting cations. This invention tested the HEO material prepared in Example 1 against multiple competing ions (K... + Na + Ca 2+ Cu 2+ Zn 2+ Ba 2+ The uranium removal performance was tested under illumination (at a concentration of 50 ppm) for 45 minutes, and the uranium removal rate was measured. Results are shown below. Figure 10 (Initial concentration of uranium and its corresponding competing ions, CM = 50 ppm) These common ions did not significantly inhibit the removal efficiency of U(VI). This excellent anti-interference ability is closely related to the material's mechanism of action: since the fixation of U(VI) is mainly achieved through H2O2 generated in the solution phase, rather than relying on competitive adsorption on the catalyst surface, the occupation of surface sites by coexisting ions does not directly affect the final removal effect. This highlights the unique advantages of this HEO material in treating wastewater with complex compositions.
[0087] 5. Effect of different molar ratios of rare earth components on the photocatalytic uranium removal performance of the material
[0088] The material obtained in Example 1 and the materials obtained in Comparative Examples 1-18 with different molar ratios of rare earth components were subjected to photocatalytic uranium removal performance tests. The uranium removal rate was tested after 45 minutes of illumination, and the results are as follows: Figure 11 As shown, these materials generally have the ability to remove uranyl ions from solution under light, and Example 1 is the best.
[0089] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic materials, characterized in that: Includes the following steps: (1) Take rare earth salts and add them to a solvent, and stir to form a homogeneous rare earth salt solution, wherein the rare earths include Y, La, Sm, Er, Yb and Ce; (2) Add hydrothermal auxiliary agent to the rare earth salt solution obtained in step (1), mix well, and obtain a mixed solution; (3) The mixed solution obtained in step (2) is subjected to hydrothermal reaction. After the reaction is completed, it is naturally cooled, the precipitate is collected, washed and dried to obtain precursor powder; (4) Heat-treat the precursor powder obtained in step (3) to obtain the YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material.
2. The preparation method according to claim 1, characterized in that: In step (1), the salt is any one or more of nitrates, chlorides, sulfates, acetates, acetylacetones, and carbonates, the molar ratio of Y, La, Sm, Er, Yb, and Ce is (1~5):(1~5):(1~5):(1~5):(1~5):(1~5), the solvent is one or more of water, ethanol, methanol, N,N-dimethylformamide, and dioxane, and the ratio of the molar amount of the rare earth salt to the volume of the solvent added is 1 mmol:(3~10) mL.
3. The preparation method according to claim 1, characterized in that: In step (2), the hydrothermal auxiliary agent is urea, and the molar ratio of urea to rare earth salt is not less than 2:
1.
4. The preparation method according to claim 1, characterized in that: In step (3), the conditions for the hydrothermal reaction include: temperature 100~150℃ and time 12~48h.
5. The preparation method according to claim 1, characterized in that: The heat treatment conditions in step (4) include: a heating rate of 0.3~1.0℃ / min, a temperature of 500~800℃, and a holding time of 8~15h.
6. The preparation method according to claim 2, characterized in that: In step (1), the salt is a nitrate, the molar ratio of Y, La, Sm, Er, Yb and Ce is 1:1:1:1:1:1, and the solvent is water.
7. The preparation method according to claim 5, characterized in that: The heat treatment conditions in step (4) include: a heating rate of 0.5~0.8℃ / min, a temperature of 550~650℃, and a holding time of 9~12h.
8. A YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material obtained by the preparation method according to claim 1.
9. The application of a YLaSmErYbCeO hexa-rare earth high-entropy oxide photocatalytic material obtained by the preparation method according to claim 1 for the removal of uranyl ions.
10. The application according to claim 9, characterized in that: The YLaSmErYbCeO hexa-element rare earth high-entropy oxide photocatalytic material was placed in wastewater containing uranyl ions and carried out a photocatalytic reaction under light irradiation conditions. The concentration of uranyl ions in the wastewater was 10~500 mg / L, and the amount of YLaSmErYbCeO hexa-element rare earth high-entropy oxide photocatalytic material added was 200~800 mg / L.
